2010
DOI: 10.1007/s12098-010-0115-0
|View full text |Cite
|
Sign up to set email alerts
|

Human touch to detect hypothermia in neonates in Indian slum dwellings

Abstract: HT emerged simpler and programmatically feasible. There is a need to examine whether trained and supervised community-based health workers and mothers can use HT accurately to identify and manage hypothermia and other simple signs of newborn illness using minimal algorithm at home and more confidently refer such newborns to proximal facilities linked to the program to ensure prompt management of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Studies in India and Nepal have shown human touch to be reasonably reliable for the detection of hypothermia when health workers were trained for these investigations. [45][46][47][48][49] Mothers, however, seem to have a far lower sensitivity than health workers. Only 24% of mothers in India were able to correctly identify hypothermia.…”
Section: Diagnosismentioning
confidence: 99%
“…Studies in India and Nepal have shown human touch to be reasonably reliable for the detection of hypothermia when health workers were trained for these investigations. [45][46][47][48][49] Mothers, however, seem to have a far lower sensitivity than health workers. Only 24% of mothers in India were able to correctly identify hypothermia.…”
Section: Diagnosismentioning
confidence: 99%
“…1 In India, the prevalence of hypothermia varies widely but recent estimates in normal newborns in community settings are around 31% and about 32% in hospital settings, but these included mostly normal weight newborns. 2,3 The prevalence can be estimated to be even higher for low birth weight newborns. Approximately 27 Jagadish AS et al Int J Contemp Pediatr.…”
Section: Introductionmentioning
confidence: 99%
“…Ellis et al ( 15 ) emphasize the need for further palpation and monitoring if the baby is thought to be cold based on human touch. The accuracy of human touch increases when conducted by trained workers ( 14 , 17 ) and pediatricians ( 18 ), with all pediatricians in one study found to be capable of correctly identifying all hypothermic babies.…”
Section: Resultsmentioning
confidence: 99%